TAXATION: A FUNCTION OF ECONOMIC INCENTIVES OR A BURDEN ON THE CITIZENS - Mustafa Mahdi Abdulridha (Universitas Negeri Malang, 2026)
Taxes can be seen as one of the most significant gears for funding public offers, for redistributing wealth, and for stabilizing economies. But they often communicate a price too high for who the price has the largest impact on and the community. This paper analyzes those different features of taxation both as a monetary tool and as a contributing cause to citizens' wellbeing. The work is titled descriptive and goal method and strives to explore the effect of taxing increase, inequality of revenue and the welfare of society. These effects imply that although taxes are the major source of funding for the state, the functioning of taxes and their being received by the society is determined through methods of every tax policy as well as the interaction capability of the institutions in public expenditure; aggregate economic conditions.